Cornsilk (Zea mays Hairs) improves nutrient, physical traits without affecting sensory properties of chicken patties - Wan Rosli .W.I,; Nurhanan .A.R,; Solihah .M.A,; Mohsin .S.S.J, (Universiti Kebangsaan Malaysia, 2011)
The proximate analyses, physical traits and sensory properties of chicken patties incorporated with different levels of cornsilk dietary fibre were studied. The patties were formulated with 2%, 4% and 6% dried ground cornsilk. The protein content increased in line with the cornsilk level in both raw and cooked chicken patties. Cooked chicken patties incorporated with 6% cornsilk showed the highest protein concentration at 28.42% and the lowest fat concentration at 14.60%, respectively. All cooked patty samples recorded moisture content ranging from 42.73-46.40%. Patty formulated with 6% cornsilk recorded the highest cooking yield at 83.03%. Cornsilk fibre has been successful in improving cooking yield and in retaining moisture and fat of chicken patties. The addition of cornsilk fibre does not change the sensory properties and the acceptability of chicken patties.